Faculty Development in Medical Education - Uddin, Md Mokhles; Yusuff, Sazzad Mohammad; Mitra, Tapash; Awal, Abdul; Chowdhury, Ali Asgar (Journal of Chittagong Medical College Teachers' Association, 2016)
Faculty refers to those who teachers. It is defined as group of body of peoples, specially teachers, professors and lecturers with a common duty or obligation which is to teach at a certain educational institution. They are the academic staff of the institution and also called the teaching staff. They are specialized in various fields of study and teachers different subjects at the institution. Faculty development is the personal and professional development of teachers, clinicians, researchers and administrators. JCMCTA 2016 ; 27 (1) : 11 - 16